Hydrophobically modified cotton fabric assisted separation of oil-water mixture - Neha Bhatt (IWA Publishing, 2021)
Superhydrophobic-superoleophilic fabrics were prepared and evaluated for oil–water mixture separation efficiencies. The nano-TiO2 and nano-SiO2 based coatings were done on the surface of the cotton fabric to create nanoscale roughness over the surface which was further modified by low energy material 1, 1, 3, 3-Hexamethyldisilazane (HMDS) and, polydimethylsiloxane (PDMS). Particle size and stability of prepared sol were characterized by particle size analysis and zeta potential. Coated cotton fabric samples were characterized by contact angle, contact angle hesteresis and surface free energy for its hydrophobic nature. Surface morphology was studied by scanning electron microscopy (SEM). The coated fabrics were found to be hydrophobic with low surface free energy values. The maximum contact angle was found to be 133° and lowest contact angle hysteresis was 5°. SEM confirmed the appearance of nanoscale surface roughness after coating of sols on cotton fabric. The average particle size and zeta potential values of silica sol was 61 nm and 137 mv whereas for titania sol it was found 344 nm and 200 mv, respectively. The oil–water separation efficiency of coated fabric was also observed by a different oil–water mixture. The coatings were found to be hydrophobic in nature and seem to be very useful for oil–water mixture separation. HIGHLIGHTS Nanosilica (SiO2) and nanotitania (TiO2) were used for hydrophobic-oleophilic coating.; Sols were hydrophobically modified with HMDS and PDMS.; Sols were coated on fabric, to create roughness over the surface.; Coated fabrics were characterized by SEM and contact angle measurements.; Application of coated surface for oil–water separation was performed.; More than 80% of efficiency towards different oil–water mixture.;